The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3109/14017431.2015.1098725
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels predict hospitalization and mortality in patients with heart failure

Abstract: Vitamin D deficiency is highly prevalent in patients with HF, and low vitamin D levels are closely associated with increased hospitalisation and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(27 reference statements)
2
8
0
Order By: Relevance
“…After adjusting for multiple confounders, the outcome data from the cohort study are consistent with previous smaller reports in ambulatory patients [9,21,22], hospitalised patients [10] and registry data [3,6,23], and reveal increased mortality in patients with low 25[OH]D concentrations compared with those without. In all of these previous studies, 25[OH]D deficiency was less frequent than in our cohort ranging from 28 to 75% [10,24], whilst overall mortality of the cohorts was higher.…”
Section: Discussionsupporting
confidence: 79%
“…After adjusting for multiple confounders, the outcome data from the cohort study are consistent with previous smaller reports in ambulatory patients [9,21,22], hospitalised patients [10] and registry data [3,6,23], and reveal increased mortality in patients with low 25[OH]D concentrations compared with those without. In all of these previous studies, 25[OH]D deficiency was less frequent than in our cohort ranging from 28 to 75% [10,24], whilst overall mortality of the cohorts was higher.…”
Section: Discussionsupporting
confidence: 79%
“…A significant high prevalence of vitamin D deficiency in patients with HF, when comparing low and very low vs. normal serum 25(OH)D levels (HR = 1.33 and 2.19, respectively), has been found [31]. A high prevalence of vitamin D deficiency among patients with HF and an independent association of low 25(OH)D levels with hospitalization and mortality rates have also been described [32]. On the other hand, in a different type of study to evaluate whether inadequate serum levels of 25(OH)D predict the prevalence of chronic conditions such as cardiovascular disease, type 2 diabetes, and obesity, among others, no association with any chronic condition, including heart failure, was found; this study did not report prevalence of vitamin D deficiency [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, obese people are more prone to vitamin D deficiency, both obesity and vitamin D deficiency were independent risk factors for heart failure [ 44 ]. Another well-organized RCT from 2016 examined the role of vitamin D in predicting the rate of hospitalizations and mortality in HF patients [ 45 ]. This study finally concluded vitamin D as an independent predictor of hospitalizations and the risk of mortality [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…Another well-organized RCT from 2016 examined the role of vitamin D in predicting the rate of hospitalizations and mortality in HF patients [ 45 ]. This study finally concluded vitamin D as an independent predictor of hospitalizations and the risk of mortality [ 45 ]. The limitations of this study were the small sample size and small control group.…”
Section: Reviewmentioning
confidence: 99%